Improving the Students Reading Comprehension by Using Graphic Organizer at the Second Grade Students of SMP Universitas Muhammadiyah Makassar - Fatmajayanti, Fatmajayanti; Patahuddin, Patahuddin; A, Nasrullah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
The problem statement of this research is “Can the use graphic organizer improve the students reading comprehension at the second grade students of SMP universitas muhammadiyah makasar?” The objective of the research is to find out whether or not the use of graphic organizer can improve the reading comprehension of the second grade students of SMP universitas Muhammadiyah Makassar. This research employed Quasi-Experimental method that applied experimental and control class.The population was the second grade students of SMP Universitas Muhammadiyah Makassar 2019-2020 academic years. Total number of population was 40 students , they are class VIII. A as experimental class consisted of 20 students and class VIII. B as control class consisted of 20 students. The instrument used in this research was graphic organizer methode. The result of this research showed that the experimetal group got mean score (69,5) while the control class group got (57,5). This showed that there was improvement the students who were taught by using graphic organizer method. The result of the t-test value (4,379) was higher than t –table (1,685), this means that was accepted and was rejected .The students who taught by using graphic organizer were better than konventional srategy.